The Impact Of Religion On The Consumption Patterns Of Poor Muslim Families In Lengayang District, Pesisir Selatan Regency, Sumatra Barat Province From An Sharia Economic Perspective - Afriyanti, Afriyanti; Anshari, Fauzan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
Pesisir Selatan Regency is the second poorest region in West Sumatra, with a poverty rate that has remained steady at an average of 7% from 2018 to 2022. This study aims to explore the impact of religion on poor Muslim households in the Lengayang District of Pesisir Selatan. Using a qualitative descriptive research method, the study involved 150 respondents. Data was collected through documentation, in-depth interviews, questionnaires, and analysis of interview results.The findings show that religion positively influences the consumption patterns of poor Muslim families in Lengayang. These families practice selective consumption, choosing only necessary items that are halal, clean, simple, and not excessive. This behavior aligns with Islamic principles and is influenced by their low and irregular income, as well as the rural lifestyle. The spiritual life of the community is deeply rooted in Islamic traditions and teachings, which guide their daily lives. However, the study also found some negative impacts. Many people express frustration over the high costs of education and living, as well as dissatisfaction with government support. They feel that assistance is insufficient and often misdirected. Some are skeptical and no longer trust that filing complaints will bring any positive change, as they have seen little improvement over time.